2008
DOI: 10.1590/s0100-83582008000300016
|View full text |Cite
|
Sign up to set email alerts
|

Influência do período de cultivo do capim-pé-de-galinha-gigante (Eleusine coracana) na fitorremediação de solo contaminado com picloram

Abstract: RESUMO -O objetivo deste trabalho foi avaliar a influência do período de cultivo do capimpé-de-galinha-gigante (Eleusine coracana) sobre a fitorremediação de solo contaminado com picloram. O experimento foi conduzido em casa de vegetação, no período de setembro de 2006 a fevereiro de 2007. Os tratamentos foram compostos pela combinação entre quatro períodos de cultivo da espécie vegetal Eleusine coracana (0, 60, 80 e 100 dias) e três doses do picloram (0, 80 e 160 g ha), totalizando 12 tratamentos. O delineame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…(2006), who evaluated the persistence of picloram in the soil to control some weed plants in pasture, using cucumber as a test plant, revealed a high intoxication in the biological indicator at 180 DAA. However, Carmo et al (2008b) observed satisfactory results on the intoxication percentage of tomato as a bioindicator plant, when soil was cultivated for 60 days with finger millet (Eleusine coracana), at 80 g ha -1 and 160 g ha -1 of picloram.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2006), who evaluated the persistence of picloram in the soil to control some weed plants in pasture, using cucumber as a test plant, revealed a high intoxication in the biological indicator at 180 DAA. However, Carmo et al (2008b) observed satisfactory results on the intoxication percentage of tomato as a bioindicator plant, when soil was cultivated for 60 days with finger millet (Eleusine coracana), at 80 g ha -1 and 160 g ha -1 of picloram.…”
Section: Resultsmentioning
confidence: 99%
“…Various forage species, such as Eleusine coracana, brachiaria and Panicum maximum, have been used in picloram phytoremediation programs (Santos et al 2006, Belo et al 2007a, Carmo et al 2008aand 2008b, Pires et al 2008. Santos et al (2013) studied the sensitivity of three species (beet, cucumber and tomato) for 2.4 D and picloram to be used as indicators and concluded that beet and tomato are more sensitive, and the symptoms of visual intoxication ranged for assessing the presence of herbicide residues.…”
Section: Palavras-chavementioning
confidence: 99%